Role of Small Intestine and Gut Microbiome in Plant-Based Oral Tolerance for Hemophilia - Kumar, Sandeep R. P.; Wang, Xiaomei; Avuthu, Nagavardhini; Bertolini, Thais B.; Terhorst, Cox; Guda, Chittibabu; Daniell, Henry; Herzog, Roland W. (Frontiers in Immunology, 2020)
Fusion proteins, which consist of factor VIII or factor IX and the transmucosal carrier cholera toxin subunit B, expressed in chloroplasts and bioencapsulated within plant cells, initiate tolerogenic immune responses in the intestine when administered orally. This approach induces regulatory T cells (Treg), which suppress inhibitory antibody formation directed at hemophilia proteins induced by intravenous replacement therapy in hemophilia A and B mice. Further analyses of Treg CD4+ lymphocyte sub-populations in hemophilia B mice reveal a marked increase in the frequency of CD4+CD25−FoxP3−LAP+ T cells (but not of CD4+CD25+FoxP3+ T cells) in the lamina propria of the small but not large intestine. The adoptive transfer of very small numbers of CD4+CD25−LAP+ Treg isolated from the spleen of tolerized mice was superior in suppression of antibodies directed against FIX when compared to CD4+CD25+ T cells. Thus, tolerance induction by oral delivery of antigens bioencapsulated in plant cells occurs via the unique immune system of the small intestine, and suppression of antibody formation is primarily carried out by induced latency-associated peptide (LAP) expressing Treg that likely migrate to the spleen. Tolerogenic antigen presentation in the small intestine requires partial enzymatic degradation of plant cell wall by commensal bacteria in order to release the antigen. Microbiome analysis of hemophilia B mice showed marked differences between small and large intestine. Remarkably, bacterial species known to produce a broad spectrum of enzymes involved in degradation of plant cell wall components were found in the small intestine, in particular in the duodenum. These were highly distinct from populations of cell wall degrading bacteria found in the large intestine. Therefore, FIX antigen presentation and Treg induction by the immune system of the small intestine relies on activity of a distinct microbiome that can potentially be augmented to further enhance this approach.